NaCl and Na2SO4 solution effect on weathering steel visual appearance when the ambient temperature changes cyclically. Issue 1 (1st January 2019) - Daukšys, Mindaugas; Bytautaitė, Evelina; Mockienė, Jūratė; Nizevičienė, Dalia
Abstract: Visual appearance—colour and texture variation—of weathering steel was compared by testing weathering steel samples in aggressive and non-aggressive conditions, and cyclical changes of ambient temperature. This paper introduces a new method for determining visual appearance of weather-resistant steel in different environmental conditions. Weathering steel samples were tested in H2 O, 3% NaCl and 3% Na2 SO4 solutions under ambient temperature changing from +20°C to −20°C per day. The structure of steel surface viewed under optical microscope revealed corrosion products in all steel samples. X-ray diffraction analysis of corrosion products revealed the presence of oxy-hydroxides, such as lepidocrocite (ɣ-FeO(OH)), goethite (α-FeO(OH)) and magnetite (Fe3 O4 ) in different environment. Optical microscopy images of corroded surfaces had different visual appearance and orange, yellow, sandy, black or anthracite colours, which indicate that the corrosion products primarily contain lepidocrocite (ɣ-FeO(OH)), goethite (α-FeO(OH)) and magnetite (Fe3 O4 ). EDS analysis revealed that the rust of samples kept in 3% NaCl solution had the highest amount of iron ions.